Prinsip dan Ruang Lingkup Pendidikan Aqidah Akhlaq - Rohmad Qomari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Moral education is a spirit of Islamic education. The purpose of education is not merely filling student’s brain with all knowledge they’d known before, but rather to teach akhlâq to their soul, internalizing fadîlah (virtue), accustoming good manner, and prepare them to live an honesty life. The main direction of Islamic education is highly moral people, with pure spirit, strong intention, lofty inspiration and moral, know and do their responsibility and obligation, respect human right, and always remembering Allah on every their activity.